Pelatihan Kewirausahaan Bidang Fashion Pada Pelajar SMK Bhakti Nusantara: Seni Lukis Kain - Pandansari, Purwosiwi; Purwanti, Rina; Fauzi, Irsal (Universitas Merdeka Pasuruan, 2022)
Abstract:The target and outcome of this community service activity are to provide skills training using cloth painting techniques that can be practiced easily, with the finished product being t-shirts that can be used daily, and have selling power as a business product.The training approach uses simulation and practicum methods, as well as discussions on fashion themes that will be applied to clothing.After the training activities, Student XI of the Vocational High School of SMK Bhakti Nusantara, showed their interest and talent in the fashion field, combined by a good knowledge of painting techniques on cloth media.